Sexual Selection and Mixed Sex Expression: Adolescent Protandry, Phenotypic Tradeoffs and ‘Unconventional' Sex Allocation Estimates in a Protandric-Simultaneous Hermaphrodite - Baeza, J. Antonio (Frontiers in Marine Science, 2018)
Background: In protandric-simultaneous (PS) hermaphrodites, individuals invariably reproduce as males first and later in life as simultaneous hermaphrodites. Here, the shrimp Lysmata wurdemanni was used as a model to (i) test for the role of sexual selection (male-male competition) in explaining the early male phase and size-dependent sex allocation (SDSA) in PS hermaphrodites, (ii) examine the tradeoff between the male and female function in hermaphrodites, and (iii) determine if SDSA also takes place in the form of sex-specific behaviors and anatomical structures. Results: In L. wurdemanni, male mating ability was size- and sex-dependent; greater for small than for large hermaphrodites and for males than hermaphrodites matched in body size. The above explains the adaptive value of the early male phase in PS hermaphrodites; small individuals should speed up sperm production and delay female reproduction to profit from male mating opportunities that are the greatest when small. Size-dependent male mating ability also suggests that small hermaphrodites should produce proportionally more sperm than ova compared to large hermaphrodites, a prediction supported by data. Sex allocation, measured as sex-specific behaviors and anatomical structures, was also size-dependent. No tradeoff between ova and sperm mass was found. However, among-individual variation in resource acquisition was considerable, suggesting that the observed lack of a statistical relationship between sperm and ova mass does not necessarily imply the absence of sex allocation tradeoffs in L. wurdemanni. Conclusion: Sexual selection is most relevant in PS hermaphrodites, SDSA also involves sex-specific behaviors and morphological features, and variation in resource acquisition and allocation can explain the apparent absence of sex allocation tradeoffs.